PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PT. SAKURA ANUGRAH PRATAMA - Febri Setianingsih; Rully Arifiansyah (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of service quality, price perception, and promotion on customer satisfaction at PT. Sakura Anugrah Pratama. This descriptive quantitative research used a questionnaire as the data collection instrument. A sample of 100 respondents was selected using purposive sampling, with the criteria of having made a service purchase two or more times. The data were analyzed using multiple linear regression with the help of the SPSS application. The research findings indicate that service quality, price perception, and promotion both partially and simultaneously, have a positive and significant influence on customer satisfaction. These findings highlight the importance of maintaining and improving service quality, managing price perception, and optimizing promotions to enhance overall customer satisfaction.